Can leaders, teamwork, and technological capability boost Indonesian bankers' performance? - Kusumaningrum, Reny; Santoso, Adi; Kristyana, Naning (Universitas Negeri Surabaya, Indonesia, 2023)
This research aims to find out the effect of technology capability, leadership support, and teamwork support on employee performance in Indonesian banking sector. The number of samples in this study was 300 bank employees. Data collection uses a questionnaire that is distributed online using Google Forms. Data measurement uses a five-point Likert scale and data processing uses Structural Equation Modelling (SEM). This study found that leadership support has no significant effect on employee performance, while technology capability and teamwork support significantly affect employee performance. Based on the research results, banking companies must focus on improving employee performance, such as increasing employee capabilities and creating a healthy environment for employees to improve and be comparable to increasing company performance in achieving goals. The managerial implication of this study suggests team leaders improve performance by empowering employees, communicating a vision that motivates employees to work harder, and clarifying goals, roles, and rewards. At the supervisory level, a team leader may boost team performance by understanding employee needs, providing support, and building confidence.